High-throughput study of the structural stability and thermoelectric properties of transition metal silicides - Ingo Opahle; Alessandro Parma; Eunan J McEniry; Ralf Drautz; Georg K H Madsen (New Journal of Physics, 2013)
The phase stability, electronic structure and transport properties of binary 3d, 4d and 5d transition metal silicides are investigated using high-throughput density functional calculations. An overall good agreement is found between the calculated 0 K phase diagrams and experiment. We introduce descriptors for the phase-stability and thermoelectric properties and hereby identify several candidates with potential for thermoelectric applications. This includes known thermoelectrics like Mn _4 Si _7 , β -FeSi _2 , Ru _2 Si _3 and CrSi _2 as well as new potentially meta-stable materials like Rh _3 Si _5 , Fe _2 Si _3 and an orthorhombic CrSi _2 phase. Analysis of the electronic structure shows that the gap formation in most of the semiconducting transition metal silicides can be understood with simple hybridization models. The transport properties of the Mn _4 Si _7 , Ru _2 Ge _3 and Ir _3 Si _5 structure types and the orthorhombic CrSi _2 phase are discussed. The calculated transport properties are in good agreement with available experimental data. It is shown that a better thermoelectric performance may be achieved upon optimal doping. Finally, the high-throughput data are analysed and rationalized using a simple tight-binding model.